Ataxia Telangiectasia Diagnosed on Newborn Screening–Case Cohort of 5 Years' Experience - Mandola, Amarilla B.; Reid, Brenda; Sirror, Raga; Brager, Rae; Dent, Peter; Chakroborty, Pranesh; Bulman, Dennis E.; Roifman, Chaim M. (Frontiers in Immunology, 2019)
Ataxia telangiectasia (AT) is a genetic condition caused by mutations involving ATM (Ataxia Telangiectasia Mutated). This gene is responsible for the expression of a DNA double stranded break repair kinase, the ATM protein kinase. The syndrome encompasses combined immunodeficiency and various degrees of neurological abnormalities and increased risk of malignancy. Typically, patients present early in life with delay in neurological milestones, but very infrequently, with life threatening infections typical of a profound T cell deficiency. It would therefore be unexpected to identify this condition immediately after birth using T cell receptor excision circle (TREC) based newborn screening (NBS) for SCID. We sought to evaluate the frequency of AT detected by NBS, and to assess immunity as well as the genetic aberrations associated with this early presentation. Here, we describe the clinical, laboratory, and genetic features of patients diagnosed with AT through the Ontario NBS program for SCID, and followed in our centre since its inception in 2013. Four patients were diagnosed with AT as a result of low TRECs on NBS. In each case, whole exome sequencing was diagnostic. All of our patients had compound heterozygous mutations involving the FRAP-ATM-TRRAP (FAT) domain of the ATM gene, which appears critical for kinase activity and highly sensitive to mutagenesis. Our patients presented with profound lymphopenia involving both B and T cells. The ratio of naïve/memory CD45+RA/RO T cells population was variable. T cell repertoire showed decreased T cell diversity. Two out of 4 patients had decreased specific antibody response to vaccination and hypogammaglobulinemia requiring IVIG replacement. In 2 patients, profound decreased responses to phytohemagglutinin stimulation was observed. In the other 2 patients, the initial robust response declined with time. In summary, the rate of detection of AT through NBS had been surprisingly high at our center. One case was identified per year, while the total rate for SCID has been 5 new cases per year. This early detection may allow for better prospective evaluation of AT shortly after birth, and may assist in formulating early and more effective interventions both for the neurological as well as the immune abnormalities in this syndrome.